A new case of UDP‐galactose transporter deficiency (SLC35A2‐CDG): molecular basis, clinical phenotype, and therapeutic approach. Issue 5 (17th March 2015) - Dörre, K.; Olczak, M.; Wada, Y.; Sosicka, P.; Grüneberg, M.; Reunert, J.; Kurlemann, G.; Fiedler, B.; Biskup, S.; Hörtnagel, K.; Rust, S.; Marquardt, T.
Abstract: Congenital disorders of glycosylation (CDG) are a group of hereditary metabolic diseases characterized by abnormal glycosylation of proteins and lipids. Often, multisystem disorders with central nervous system involvement and a large variety of clinical symptoms occur. The main characteristics are developmental delay, seizures, and ataxia. In this paper we report the clinical and biochemical characteristics of a 5‐year‐old girl with a defective galactosylation of N‐glycans, resulting in developmental delay, muscular hypotonia, epileptic seizures, inverted nipples, and visual impairment. Next generation sequencing revealed a de novo mutation (c.797G > T, p.G266V) in the X‐chromosomal gene SLC35A2 (solute carrier family 35, UDP‐galactose transporter, member A2; MIM 300896). While this mutation was found heterozygous, random X‐inactivation of the normal allele will lead to loss of normal SLC35A2 activity in respective cells. The functional relevance of the mutation was demonstrated by complementation of UGT‐deficient MDCK‐RCA r and CHO‐Lec8 cells by normal UGT‐expression construct but not by the mutant version. The effect of dietary galactose supplementation on glycosylation was investigated, showing a nearly complete normalization of transferrin glycosylation.